PERANCANGAN PENILAIAN KINERJA PERUSAHAAN MENGGUNAKAN BALANCED SCORECARD BERBASIS DIGITAL PADA PERUSAHAAN TEKSTIL DI CIREBON - Dewi, Isti Riana; Puspitarini, Dewi Anggun (Fakultas Ekonomi dan Bisnis, 2024)
Hanjani Group is a company related to the textile industry. In the performance evaluation process, currently there is no system that can enter all sales data at each branch of the company. The proposed solution is creating a website using the balanced scorecard method that allows the evaluation process to be presented with practical nominal results in performance assessment when viewed from four perspectives, there are finance, customers, internal business processes, and growth. This website provides a better view that managers will use to conduct statistical processes and compare systems from various branches of the company because it allows for integration or connection between disciplines. Elements of system analysis and design are explained using context diagrams, flowcharts, DFDs, and ERDs. The steps taken by designing a software system using PHP (metatext preprocessor) as the translation language and MySQL as the database manager. After testing by the company owner, this website can load performance evaluation reports at various branches of the company in Hanjani Group. Key words: Performance Assessment, Balanced Scorecard, Hanjani Group